Electromagnetic and thermal analysis of high-Tc superconductor in application of current limiting devices - Wai S.K.; Hamid N.A.; Selamat N.S.; Yew P.J.; Ismail A.B.; Ahmad B. (2023)
Superconducting fault current limiters (SCFCL) offer an attractive way to limit short-circuit currents in power systems. Analysis into electromagnetic and thermal behaviors of superconductor material is crucial in order to develop a novel design concept of a fault current limiter. A new scheme, which can treat electromagnetic field of the type-II superconductor under transient temperature field, is proposed. In this analysis, one of the critical state models, the Bean model was employed to determine the current distribution in the superconductors and effect of magnetic flux flow was also taken into account. Numerical results indicate that the flux flow strongly affects the stability against the quench in Bi-2212 material. High-Tc superconductor material (Bi-2212) was chosen for the current limiting application. In order to investigate characteristics of the current-quenched Bi-2212 bulk, a 2-dimensional heat transfer equation was numerically solved using the finite element simulation. Heat distributions among the superconductor bars were also simulated and by comparing both the experimental and simulated results, it was found that non-uniformities in a current density or a temperature may exist in the quenching of bulk Bi-2212 superconductor. 2007 Springer Science+Business Media, LLC.